Combination of Somaclonal Variation and Mutagenesis for Crop Improvement - Lestari, Endang G. (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2012)
Mutation-basedplant improvement, which changes one or a few specifictraits of a cultivar, can contribute to crop improvement.Tissue culture increases the efficiency of mutagenictreatment to induce variations. In vitro culture incombination with induced mutation can speed up thebreeding program by generating variability, followed byselection and multiplication of the desired genotypes. Inmany vegetative propagated crops, mutation induction incombination with in vitro culture techniques can be themost effective method for plant improvement. In seedpropagated species, the application of mutation coupledwith doubled haploid systems seems to be highly promisingin crop improvement. This approach speeds up the breedingprogram through generation of variability followed byselection of homozygousity and rapid multiplication ofdesired genotypes.